PENGARUH MODEL NUMBERED HEAD TOGETHER BERBANTUAN GEOGEBRA TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Koyumah, Siti; Utomo, Rukmono Budi (JURNAL e-DuMath, 2016)
The study purpose to find out the differences in mathematical learning with using cooperative Numbered Head TogetherI (NHT) learning model aided by geogebra on the students problem solving ability in mathematical learning in SMPN 3 Pasar Kemis. This is research use experimental method and control, the quantitative research design with nonequivalent control grup design. Population in this research were student of class VII. The collection techniques samples using purposive sampling. The research shows that there any different between the problem solving ability in rectangular and student by learning model NHT aided Geogebra to student who were given conventional learning model. Keywords : Numbered Head Together, Geogebra, Mathematical Problem Solving